A coupled Bio-EF process for mineralization of the pharmaceuticals furosemide and ranitidine: Feasibility assessment. (July 2016) - Olvera-Vargas, Hugo; Oturan, Nihal; Buisson, Didier; Oturan, Mehmet A.
Abstract: A coupled Bio-EF treatment has been applied as a reliable process for the degradation of the pharmaceuticals furosemide (FRSM) and ranitidine (RNTD) in aqueous medium, in order to reduce the high energy consumption related to electrochemical technology. In the first stage of this study, electrochemical degradation of the drugs was assessed by the electro-Fenton process (EF) using a BDD/carbon-felt cell. Biodegradability of the drugs solutions was enhanced reaching BOD5 /COD ratios close to the biodegradability threshold of 0.4, evidencing the formation of bio-compatible by-products (mainly short-chain carboxylic acids) which are suitable for biological post-treatment. Moreover, toxicity evaluation by the Microtox ® method revealed that EF pre-treatment was able of detoxifying both, FRSM and RNTD solutions, constituting another indicator of biodegradability of EF treated solutions. In the second stage, electrolyzed solutions were treated by means of an aerobic biological process. A significant part of the short-chain carboxylic acids formed during the electrochemical phase was satisfactorily removed by the used selected microorganisms. The results obtained demonstrate the efficiency and feasibility of the integrated Bio-EF process. Graphical abstract: Highlights: Oxidative degradation of drugs furosemide and ranitidine. Enhancement of biodegradability during electro-Fenton (EF) oxidation. Coupling between EF and biological treatment. Almost complete mineralization by the integrated bio-EF hybrid process. Toxicity assessment of treated solutions.